Risk factors for failure of male slings and artificial urinary sphincters: results from alLarge middle european cohort study - Hüsch, Tanja; Nyarangi-Dix, Joanne (Urologia internationalis, 2017)
Introduction: We analysed the impact of predefined risk factors: age, diabetes, history of pelvic irradiation, prior surgery for stress urinary incontinence (SUI), prior urethral stricture, additional procedure during SUI surgery, duration of incontinence, ASA-classification and cause for incontinence on failure and complications in male SUI surgery. Materials and Methods: We retrospectively identified 506 patients with an artificial urinary sphincter (AUS) and 513 patients with a male sling (MS) in a multicenter cohort study. Complication rates were correlated to the risk factors in univariate analysis. Subsequently, a multivariate logistic regression adjusted to the risk factors was performed. A p value <0.05 was considered statistically significant. Results: A history of pelvic irradiation was an independent risk factor for explantation in AUS (p < 0.001) and MS (p = 0.018). Moreover, prior urethral stricture (p = 0.036) and higher ASA-classification (p = 0.039) were positively correlated with explantation in univariate analysis for AUS. Urethral erosion was correlated with prior urethral stricture (p < 0.001) and a history of pelvic irradiation (p < 0.001) in AUS. Furthermore, infection was correlated with additional procedures during SUI surgery in univariate analysis (p = 0.037) in MS. Conclusions: We first identified the correlation of higher ASA-classification and explantation in AUS. Nevertheless, only a few novel risk factors had a significant influence on the failure of MS or AUS.